When seeing stigma creates paternalism: Learning about disadvantage leads to perceptions of incompetence. (August 2022) - Reeves, Stephanie L.; Tse, Crystal; Logel, Christine; Spencer, Steven J.
The present research examines the conditions under which educating non-stigmatized individuals about the experiences of members of stigmatized groups leads to paternalistic or more respectful views of the target. We propose that when these efforts ask members of non-stigmatized groups to focus only on the difficulties experienced by stigmatized targets, they will lead to more paternalistic views of targets because they portray targets as being in need of help. In contrast, we propose that when these efforts take a broader focus on stigmatized targets and include their resilience in the face of their difficulties, they will lead to more respectful views of targets. Four studies supported these predictions. Across studies, White participants who focused only on a Black target's difficulties subsequently perceived the target as more helpless and less competent than controls. Participants who focused on the target's resilience in the face of difficulties perceived him as more competent.